Prediction-based control for a class of unstable time-delayed processes by using a modified sequential predictor. (August 2020) - Hernández–Pérez, M.A.; Fragoso–Rubio, V.; Velasco–Villa, M.; del Muro–Cuéllar, B.; Márquez–Rubio, J.F.; Puebla, H.
Abstract: This work presents a prediction-based scheme to control a class of unstable delayed (bio)-chemical processes. The main characteristic of the control scheme is that it is based on a predicted future state that is estimated using a prediction-observation protocol that allows compensating large time-delays. The convergence of the prediction error is shown through standard stability arguments. The stability of the closed-loop system is shown by invoking the separation principle between the prediction error and the control based on estimated variables feedback. Four numerical examples are used to illustrate our results, including two time-delayed benchmark case studies taken from the control process literature. Highlights: Prediction-based scheme to control a class of unstable delayed biochemical processes Prediction-based scheme works by using a modified sequential predictors The scheme offers the possibility of compensating systems without limit in time-delay An improvement over the proposed scheme is presented to deal with model uncertainties Four numerical examples from the control process literature illustrate our results